Stratosphere–troposphere exchange (STE) in the vicinity of North Atlantic cyclones - Reutter, P.; Škerlak, B.; Sprenger, M.; Wernli, H. (Atmospheric Chemistry and Physics, 2015)
It is well known that the storm tracks are a preferred region of stratosphere–troposphere exchange (STE), but a systematic and climatological investigation of the connection between cyclones and STE has not yet been performed. We use two ERA-Interim climatologies of STE and cyclones for the years 1979–2011 to quantify the amount of STE that occurs during the life cycle of North Atlantic cyclones. A Lagrangian method serves to identify individual STE events, and a sophisticated cyclone identification tool detects cyclones, their shape and size from the sea-level pressure (SLP) field and from geopotential height anomalies at 300–700 hPa. Combining the two data sets reveals that roughly 50–60 % of the total STE in the North Atlantic occurs in the vicinity of cyclones and that both downward and upward fluxes of mass across the tropopause (STT and TST, respectively) are more intense in deeper cyclones (lower minimum SLP) compared to less intense cyclones. In summer, STT and TST in the vicinity of cyclones are almost equal; in the other seasons, STT is larger by 25–60 %. Compared to climatology, cross-tropopause mass fluxes are enhanced by a factor of about 1.29 and 1.06 for STT and TST, respectively, when a cyclone is present. On average, STE is strongest during the mature phase of cyclones, i.e., in a 24 h time window around the time of maximum intensity. Systematic patterns of exchange locations relative to the cyclone centre are identified via composite analysis and shed light on the different characteristics of STT and TST. During cyclone intensification and in the mature stage, TST is mainly confined to the cyclone centre, whereas STT occurs mainly in a region further southwest. During the decay of the cyclones, both STT and TST are most frequent close to the cyclone centre, in a region with a fairly low tropopause.